Evaluation of carbon incorporation and strain of doped MgB2 superconductor by Raman spectroscopy. - Yeoh, W. K.; Zheng, R. K.; Ringer, S. P.; Li, W. X.; Xu, X.; Dou, S. X.; Chen, Soo kien; MacManus-Driscoll, J. L. (Elsevier, 2011)
Raman spectroscopy is employed to study both the strain and the carbon substitution level in SiC-doped MgB2 bulk samples. Raman spectroscopy was demonstrated to be a better method to distinguish the individual influences of strain and carbon than standard X-ray diffraction. It is found that the lattice parameter correlation method for C content determination is invalid for highly strained samples. Our result also provides an alternative explanation for lattice variation in non-carbon-doped MgB2, which is basically due to lattice strain.